Integrating music and language contents and skills in the academic course English language for children through songs and movement - Stošić, Aleksandra; Janković, Nataša (Inovacije u nastavi : časopis za savremenu nastavu, 2020)
A song is a musical content in which melody and poetic text are unified, which makes it an ideal tool in all music activities with children of preschool and early primary school age. It also represents the core of integration of different school subjects, with a huge educational potential in language teaching (both mother tongue and foreign languages). In this paper we elaborate on the advantages of integrating English Language and Music Education academic courses in working with pre-service primary and preschool teachers who are trained to teach English to preschool and early primary school children. We examine students' music experience and their preferences, as well as their familiarity with the phonological elements of the language with the aim of improving the quality of teaching. The paper also presents the key results of the research conducted in 2018 and 2019 with the first and the second generations of students attending the course English Language for Children through Songs and Movement at the first year of their studies at the Teacher Education Faculty in Belgrade. Apart from providing useful insights for further teaching, the results of the research conducted on a convenience sample of 58 students (N = 58) confirmed the importance of integrating the two academic courses by reinforcing students' vocal development in English through songs and action songs as a fundamental tool in the cross-curricular integration. The results also offer new guidelines for the future exploratory research of teaching in university education. These guidelines have a broader pedagogical significance and methodological implications for the work of the future preschool and primary school teachers.